Penerapan Electronic Government dalam Sistem Informasi Pemerintahan Daerah Sebagai Pendukung Penyelenggaraan Pemerintahan Daerah (Studi pada Pemerintah Kabupaten Sragen) - Fariha, Henni (Jurnal Administrasi Publik, 2015)
Abstract: Application of Electronic Government in information system at Local Government as Local-Government accomplishment support (Study at Government of Sragen Regency).Techonologies development which are more complex push government institution to change image of government which is considered rigid become more flexible by adopting technology values. President instruction number 3 year of 2003 mandates that government must be able form new dimension in organization, management system, and work process which are more flexible by aplying electronic government in information system at local government.Result of this research showed that application of electronic government in information system of government at Sragen Regency can be conducted effective and efficiently by using appropriate technology. Sustainability of application of local government information system at Sragen regency can be realized by using strategy which was formed by government and good will from supreme leader of Sragen regency whose mandated all of government stakeholders involve information and communication technology. Strategy which was formed through support of organization network, utilizing of information system, management system, government work process and human resources development. Keywords: Electronic Government, Information System at Local Government, Sragen Regency Abstrak: Penerapan Electronic Government dalam Sistem Informasi Pemerintahan Daerah Sebagai Pendukung Penyelenggaraan Pemerintahan Daerah (Studi pada Pemerintah Kabupaten Sragen). Perkembangan teknologi yang semakin kompleks mengharuskan lembaga pemerintahan juga harus mengubah citra pemerintahan yang dinilai kaku menjadi lebih lentur dengan mengadopsi nilai-nilai teknologi. Instruksi Presiden Nomor 3 Tahun 2003 mengamanatkan bahwa Pemerintah harus mampu membentuk dimensi baru ke dalam organisasi, sistem manajemen, dan proses kerja yang lebih lentur melalui penerapan electronic government dalam sistem informasi pemerintahan daerah.Hasil penelitian menunjukkan bahwa penerapan electronic government dalam sistem informasi pemerintahan daerah di Kabupaten Sragen dapat dilaksanakan secara efektif dan efisien dengan mengandalkan teknologi tepat guna. Keberlanjutan penerapan sistem informasi pemerintahan daerah Kabupaten Sragen dapat terwujud melalui strategi yang dibentuk oleh Pemerintah Kabupaten Sragen serta goodwill dari pimpinan tertinggi Kabupaten Sragen yang mengamanatkan seluruh penyelenggaraan pemerintahan daerah melibatkan teknologi informasi dan komunikasi. Strategi dibentuk melalui jaringan organisasi pendukung, pemanfaatan teknologi informasi, sistem manajemen dan proses kerja pemerintah, dan pengembangan kapasitas sumberdaya manusia. Kata Kunci: Electronic Government, Sistem Informasi Pemerintahan Daerah, Kabupaten Sragen